2013
DOI: 10.3382/ps.2012-02483
|View full text |Cite
|
Sign up to set email alerts
|

The effect of increasing feeding frequency on performance, plasma hormones and metabolites, and hepatic lipid metabolism of broiler breeder hens

Abstract: An experiment was conducted to study the effects of feeding regimens on reproductive performance, plasma hormone and metabolite levels, and hepatic lipid metabolism of Cobb 500 broiler breeder hens from 26 to 38 wk of age. Seventy-two birds were used in a completely randomized design with 3 treatments, each replicated 4 times. Treatments were as follows: 1) once a day feeding, in which birds were fed once a day at 0615 h (control), 2) twice a day feeding, in which daily allocated feed was fed in 2 equal meals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
1
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 31 publications
4
22
1
7
Order By: Relevance
“…This result is in line with the report of [26] who reported that productivity of the chicken could be affected by feeding frequency. At the same time the present finding is also supported by the report of [27] who indicated that twice and thrice a day feeding regimens rather than once a day improved egg production rate. The current finding also coincides with the report of [28,29] who reported that chicken fed twice a day produced more eggs compared with chicken fed once a day and the chicken received their feed 2 or 3 times per day laid 4.8 eggs more than those that fed one time per day [30].…”
Section: Discussionsupporting
confidence: 81%
“…This result is in line with the report of [26] who reported that productivity of the chicken could be affected by feeding frequency. At the same time the present finding is also supported by the report of [27] who indicated that twice and thrice a day feeding regimens rather than once a day improved egg production rate. The current finding also coincides with the report of [28,29] who reported that chicken fed twice a day produced more eggs compared with chicken fed once a day and the chicken received their feed 2 or 3 times per day laid 4.8 eggs more than those that fed one time per day [30].…”
Section: Discussionsupporting
confidence: 81%
“…They believed that increased egg weight was related to providing feed later in the day (3:00 PM). Moradi et al (2013) evaluated hens fed once a day at 6:15 AM and a twice a day feeding (at 6:15 AM and 12:15 PM) and Taherkhani et al (2010) evaluated hens fed once a day at 7:30 AM and twice a day feeding (at 7:30 AM and 11:30 AM), both authors reported that broiler breeders fed twice a day laid more and heavier eggs than those fed once a day. The influence of increasing feeding frequency may be related to a reduction in the fasting period during the day-light cycle (Moradi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Moradi et al (2013) evaluated hens fed once a day at 6:15 AM and a twice a day feeding (at 6:15 AM and 12:15 PM) and Taherkhani et al (2010) evaluated hens fed once a day at 7:30 AM and twice a day feeding (at 7:30 AM and 11:30 AM), both authors reported that broiler breeders fed twice a day laid more and heavier eggs than those fed once a day. The influence of increasing feeding frequency may be related to a reduction in the fasting period during the day-light cycle (Moradi et al, 2013). The results of this study were according to the results reported by Cave (1981), Bootwalla et al (1983) and Samara et al (1996), who reported that different feeding schedules had no effect on egg production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result differed from that in previous study in which the fasting plasma glucose levels did not differ between restricted feeding and ad libitum feeding geese (Ho et al, 2014). In broiler breeders, the plasma glucose levels immediately before feeding were lower in the birds that were fed once a day compared with the birds that were fed twice or thrice a day (Moradi et al, 2013). In the present study, the fasting plasma triacylglycerol level in Group R1 was higher than those in Groups R2 and C. The result was contrary to the previous study in which the fasting plasma triacylglycerol level in the restricted geese was lower compared with the ad libitum geese (Ho et al, 2014).…”
Section: Discussionmentioning
confidence: 99%